2019 8th International Conference on Affective Computing and Intelligent Interaction Workshops and Demos (ACIIW) 2019
DOI: 10.1109/aciiw.2019.8925052
|View full text |Cite
|
Sign up to set email alerts
|

Your Body Reveals Your Impressions about Others: A Study on Multimodal Impression Detection

Abstract: Formed impressions are crucial for human-human interaction (e.g. a job interview) and an interaction with a virtual agent/robot, since they can impact people's perceptions and willingness to be involved in the interaction. There are studies on how facial features (e.g. skin color, face shape), acoustic signals and non-verbal behaviors (e.g. gestures, postures) create/leave certain impressions. However there is little research focusing on how our bodies disclose our already formed impression of someone. Forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…To the best of our knowledge, there is only one study on assessing the formed impressions from the body signals (e.g. facial expressions and gestures) of the person forming the impression [5]. In [5], it reported that formed impressions could be detected using multimodal signals in both multi-task and single task frameworks.…”
Section: Impression and Emotion Recognitionmentioning
confidence: 99%
See 4 more Smart Citations
“…To the best of our knowledge, there is only one study on assessing the formed impressions from the body signals (e.g. facial expressions and gestures) of the person forming the impression [5]. In [5], it reported that formed impressions could be detected using multimodal signals in both multi-task and single task frameworks.…”
Section: Impression and Emotion Recognitionmentioning
confidence: 99%
“…facial expressions and gestures) of the person forming the impression [5]. In [5], it reported that formed impressions could be detected using multimodal signals in both multi-task and single task frameworks. However, which body signal reveals the formed impression more expressively was not discussed.…”
Section: Impression and Emotion Recognitionmentioning
confidence: 99%
See 3 more Smart Citations